2010
DOI: 10.1111/j.1743-7563.2010.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Oncological Society of Australia (COSA) guidelines for the safe prescribing, dispensing and administration of cancer chemotherapy

Abstract: The issue of medication safety is highly significant when anti-cancer therapy is used as a treatment modality due to the high potential for harm from these agents and the disease context in which they are being used. These guidelines provide recommendations on the safe prescribing, dispensing and administration of chemotherapy and related agents used in the treatment of cancer. The guidelines represent a multidisciplinary collaboration to standardise the complex process of providing chemotherapy for cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…• the generic drug name, number of tablets to be taken 7 and frequency and duration of therapy (written in full)…”
Section: The Pros and Cons Of Oral Cytotoxic Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…• the generic drug name, number of tablets to be taken 7 and frequency and duration of therapy (written in full)…”
Section: The Pros and Cons Of Oral Cytotoxic Therapymentioning
confidence: 99%
“…7 For cancer chemotherapy the pharmacist should have access to the treatment plan, the chemotherapy protocol and relevant patient parameters including height and weight and recent laboratory results. 10 The pharmacist should ensure that the relevant supportive medicine has been prescribed or is available to the patient.…”
Section: Dispensing and Supplying Oral Cytotoxic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the existing recommendations to ensure the safe storage, prescribing, dispensing, administration, and disposal of cytotoxic oral chemotherapy drugs are listed in the Appendix (online only). 2,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, the recommendations have not been universally accepted or incorporated into practice. Recent surveys of health care practitioners as well as patients found that the perception of oral chemotherapy being safer than intravenous chemotherapy was prevalent.…”
Section: Introductionmentioning
confidence: 99%